Wissenschaft und Wissenschaftler im Alten Ägypten Gedenkschrift für Walter Friedrich Reineke - Dils, Peter; Fischer-Elfert, Hans-Werner 1954-; Hafemann, Ingelore 1955-; Richter, Sebastian (De Gruyter, 2021)
In recent years, the histories of ancient science as well as historical epistemology have become hot topics in interdisciplinary research. This volume is a collection of essays on ancient Egyptian science and its agents. Several of the contributions focus on mathematics, the field of expertise of the Berlin Egyptologist Walter F. Reineke, the volume's honorand, but medicine, magic, astrology, botany, and chemistry are also discussed
Keywords: Reineke, Walter-Friedrich -- 1936-2015; Medizin; Wissenschaftsgeschichte; Wissenschaftstheorie; Ägyptologie; HISTORY / Ancient / Egypt; Naturwissenschaften; Mathematik; Ägypten -- Altertum; Konferenzschrift -- 2016 -- Berlin; Festschrift; Bibliografie